Chapter 8 Three Rationales for a Legal Right to Mental Integrity - Douglas, Thomas (Springer Nature, 2021)
Many states recognize a legal right to bodily integrity, understood as a right against significant, nonconsensual interference with one's body. Recently, some have called for the recognition of an analogous legal right to mental integrity: a right against significant, nonconsensual interference with one's mind. In this chapter, we describe and distinguish three different rationales for recognizing such a right. The first appeals to case-based intuitions to establish a distinctive duty not to interfere with others' minds; the second holds that, if we accept a legal right to bodily integrity, then we must, on pain of philosophical inconsistency, accept a case for an analogous right over the mind; and the third holds that recent technological developments create a need for a legal right to mental integrity.